(untitled) (European Journal of Behavioral Sciences, 2023)
Covid Pandemic impacted people across the globe, especially children who spent the most crucial years in lockdown and had to readjust themselves to the real world after the pandemic. Many children were fixated to screen devices for education, entertainment, and family interaction with limited physical socialization. The research aimed to study the impact of screen duration on language acquisition, behavioral development, social competency, and emotional regulation. The sample comprised 406 children 2-6 years old with no physical and psychological diagnosis and acquired developmental milestones at the appropriate age. Purposive sampling was conducted, and data were collected from various public and private schools and daycares. Albert Language Development Questionnaire, Strengths and Difficulties, and Social Competence (parent versions) were used to assess language development, behavioral problems, social interaction, and emotional regulation. For analysis, correlation, regression, and ANOVA were conducted. Results showed social competence and behavioral difficulties as significant predictors of Language Impairment. Increased screen exposure was found to be related to language impairment, behavioral difficulties, and poor social competence. Each of the factors was found to be significantly related, confirming our hypothesis. The results are beneficial for caregivers, teachers, and psychologists in providing guidelines about the factors. That is impairing child development especially excessive use of screen devices.